2017
DOI: 10.1259/bjr.20150836
|View full text |Cite
|
Sign up to set email alerts
|

The potential predictive value of MRI and PET-CT in mucinous and nonmucinous rectal cancer to identify patients at high risk of metastatic disease

Abstract: mEMVI could identify patients with NMC, who are at high risk of synchronous metastases. The MC group is at a high risk of developing metachronous metastases. Advances in knowledge: Patients at high risk of metastases are more likely to benefit from more aggressive neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
1
25
1
Order By: Relevance
“…Young LARC patients often present with aggressive pathological features and advanced stage compared with older patients [4][5][6]. Additionally, aggressive pathological features could result in a poorer response to NCRT [22][23][24][25][26][27][28]. Ou results are consistent with those reported by Li et.al [29] in which analysis of the Surveillance, Epidemiology, and End Results (SEER) population-based database revealed that young patients had a better prognosis than old patients.…”
Section: Discussionsupporting
confidence: 80%
“…Young LARC patients often present with aggressive pathological features and advanced stage compared with older patients [4][5][6]. Additionally, aggressive pathological features could result in a poorer response to NCRT [22][23][24][25][26][27][28]. Ou results are consistent with those reported by Li et.al [29] in which analysis of the Surveillance, Epidemiology, and End Results (SEER) population-based database revealed that young patients had a better prognosis than old patients.…”
Section: Discussionsupporting
confidence: 80%
“…What’s more, the positive detection rate of combination of m SEPT9 with CECT was higher than signal CECT and was higher than the combination of tumor marker with CECT. Thus, a validated blood-based biomarker like m SEPT9 for CRC may help to identify patients with radiologically undetectable recurrence or metastases [32].…”
Section: Discussionmentioning
confidence: 99%
“…Young LARC patients often present with aggressive pathological features and advanced stage compared with older patients [ 4 6 ]. Additionally, aggressive pathological features could result in a poorer response to NCRT [ 22 28 ]. Our results are consistent with those reported by Li et.al [ 29 ], in which analysis of the Surveillance, Epidemiology, and End Results (SEER) population-based database revealed that young patients had a better prognosis than old patients.…”
Section: Discussionmentioning
confidence: 99%